2000
DOI: 10.1177/172460080001500105
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Sel1L and Tan-1 in Normal and Neoplastic Cells

Abstract: We have previously reported on the isolation and chromosomal mapping of a novel human gene (SEL1L), which shows sequence similarity to sel-1, an extragenic suppressor of C. elegans. sel-1 functions as a negative regulator of lin-12 activity, the latter being implicated in the control of diverse cellular differentiation events. In the present study we compare the expression patterns of SEL1L and TAN-1, the human ortholog of lin-12 in normal and neoplastic cells. We found that, whereas both genes are expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…1A, panels A.1-A.3). All of these cell lines expressed SEL1L-B and -C transcripts, although at levels lower than SEL1L-A (12). In fact the SEL1L-B and -C signals in Fig.…”
Section: Cloning and Characterization Of Endogenous Sel1l-b And -C-us-mentioning
confidence: 78%
“…1A, panels A.1-A.3). All of these cell lines expressed SEL1L-B and -C transcripts, although at levels lower than SEL1L-A (12). In fact the SEL1L-B and -C signals in Fig.…”
Section: Cloning and Characterization Of Endogenous Sel1l-b And -C-us-mentioning
confidence: 78%
“…SEL1L has been reported as highly expressed in human developing and normal adult pancreas with much lower levels detected in other tissues (Biunno et al, 1997;Donoviel et al, 1998;Harada et al, 1999;Cattaneo et al, 2000). SEL1L has been also found downregulated or completely repressed in a proportion of primary adenocarcinomas of the pancreas (Biunno et al, 1997;Donoviel et al, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that SEL1L expression decreases breast cancer cell aggressiveness in vivo and in vitro and that down-regulation correlates with poor prognosis (1). Generally, SEL1L is abundantly expressed only in the pancreas (2,3) and more specifically in the acini and islets of Langerhans (4,5). However, 36% of primary pancreatic cancers do not express the gene, and a significant correlation was found with Dpc4.…”
Section: Introductionmentioning
confidence: 99%